Actual situation of Aethina tumida (Coleoptera: Nitidulidae) in Africanized honeybee colonies in Costa Rica - Calderón, Rafael (2019)
In the present study, the presence of the beetle Aethina tumida in Central American countries such as El Salvador, Nicaragua and Costa Rica is analyzed by visual sampling in which all individual frames, hive covers and bottom boards of each colony are examined. In addition, two Cutts Beetle Blaster® traps per colony were set for eight to 15 days with 25 ml of vegetable oil. The contents of the traps were examined for beetles at the Bee Pathology Laboratory of the Centro de Investigaciones Apícolas Tropicales (CINAT).